THE GREAT WILLIAM SHAKESPEARE AND HIS COMEDIES - Yusupxojayeva Sevinch Alisher qizi; Kenjayeva Muxlisa Bahodirovna (TADQIQOTLAR.UZ, 2024)
Abstract: Among playwrights, William Shakespeare is unique.It is impossible to encapsulate this amazing intellect in a few sentences.Shakespeare is arguably the greatest poet and thinker of all time, but he is not easily found.His capacity for absorption—what poet John Keats called his "negative capability"—means that his art is both generally accepting of any attitude or idea that finds there and simultaneously open to criticism and inquiry. Not only do the university wits employ popular and romantic tropes in their early comedies, but they also incorporate elements of gorgeous courtly delight and a profound grasp of the weakness and artificacies of humor.These comedies are jovial and offer a glimpse into a vibrant and creative society.